Intracellular Quantification and Localization of Label-Free Iron Oxide Nanoparticles by Holotomographic Microscopy - Friedrich, Ralf P.; Schreiber, Eveline; Tietze, Rainer; Yang, Hai; Pilarsky, Christian; Alexiou, Christoph (Nanotechnology, Science and Applications, 2020)
Background: The limitations of optical microscopy to determine the cellular localization of label-free nanoparticles prevent a solid prediction of the cellular effect of particles intended for medical applications. To avoid the strong physicochemical changes associated with fluorescent labelling, which often result in differences in cellular uptake, efficiency and toxicity of particles, novel detection techniques are required.
CRIS-Team WoS Importer:2021-01-29